2010
DOI: 10.1007/s11250-010-9543-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, haematological and biochemical alterations in heat intolerance (panting) syndrome in Egyptian cattle following natural foot-and-mouth disease (FMD)

Abstract: Clinical signs of heat intolerance (panting) syndrome were observed in Holstein cows in a private farm in Egypt. There were heat intolerance (fever), panting, profuse salivation, hirsutism, lameness and reduced milk production. Blood and serum samples were collected from ten diseased cows and five apparently healthy cows as control. Serological tests confirmed the presence of non-structural protein of foot-and-mouth disease (FMD) infection. There were significant reductions in the total red blood cell count wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 22 publications
11
32
1
Order By: Relevance
“…Significant negative correlation between calcium and phosphorus. Hyperphosphatemia was similar to that reported by Yeotikar et al (2003) and Ghanem and Abdel (2010). Hyperphosphatemia is due to higher ATP utilization and breakdown by the virus present in the body of affected animals.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Significant negative correlation between calcium and phosphorus. Hyperphosphatemia was similar to that reported by Yeotikar et al (2003) and Ghanem and Abdel (2010). Hyperphosphatemia is due to higher ATP utilization and breakdown by the virus present in the body of affected animals.…”
supporting
confidence: 89%
“…It results from hyperglycemia, and it was in the line with Yeotikar et al (2003) and Gokce et al (2004). Reduction in total protein concentrations (Ghanem and Abdel, 2010) had been reported to be associated with hepatic and renal damage, starvation, and enteropathies leading to protein loss, parasitic infestation and chronic organ diseases indicating abnormal hepatic function. Possible causes of the decreases in serum total protein concentrations observed in the study may be associated with lesions on the oral mucosa and inter digital regions.…”
mentioning
confidence: 99%
“…A significant reduction in the total number of RBCs and increase in MCV values with increased leukocytes counts in diseased group compared to their normal counterparts were found. 6,7 Our study found a significant increase in packed cell volume (PCV %) and eosinophil percentage within the positive ELISA results. RBCs count, WBCs count, lymphocyte, neutrophil, monocyte, basophil, MCV, MCH, and MCHC had no significant difference between the positive group and negative one.…”
Section: Articlesupporting
confidence: 49%
“…Furthermore only a few reports were published concerned the hematological parameters in experimental or clinical cases of FMD in cattle. [5][6][7] The goals of this current study were to investigate the prevalence of FMD in apparently healthy Awassi sheep using different diagnostic tests and to compare the hematological parameters associated with the seropositive animals for FMDV.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of anaemia could be attributed to endocrinopathy occurring secondary to viral infection (Gokce et al, 2004).The significant reduction in RBCs due to endocrinopathy is also reported by Radostits (1994). Ghanem and Hamid (2010) also reported a significant (P<0.05) decrease in RBC count in FMD affected Holstein cows. The white blood cell (WBC) count in FMD affected, recovered and apparently healthy groups were 6.55 ± 0.07, 6.73 ± 0.07 and 6.84 ±0.09X10 3 /µl respectively.…”
Section: Resultsmentioning
confidence: 78%